Long‐Lived Supramolecular Helices Promoted by Fluorinated Photoswitches. Issue 1 (12th September 2017) - Huang, He; Orlova, Tetiana; Matt, Benjamin; Katsonis, Nathalie
Abstract: Chiral azobenzenes can be used as photoswitchable dopants to control supramolecular helices in liquid crystals. However, the lack of thermal stability of the cis ‐isomer precludes envisioning the generation of long‐lived supramolecular helices with light. Here, this study demonstrates thermally stable and axially chiral azobenzene switches that can be used as chiral dopants to create supramolecular helices from (achiral) nematic liquid crystals. Their trans ‐to‐ cis photoisomerization leads to a variation of helical twisting power that reaches up to 60%, and the helical superstructure that is engineered with light displays a relaxation time that reaches tens of hours. These results demonstrate that combining ortho ‐fluorination with axial chirality in molecular photoswitches constitutes an efficient strategy to promote long‐lived helical states. Further, this approach shows potential to design supramolecular machines that are controlled by light entirely. Abstract : Azobenzene photoswitches combining ortho ‐fluorination and axial chirality are synthesized. When used as dopants in nematic liquid crystals, they promote long‐lived supramolecular helices both in the dark and under illumination.